Analysis of Improvement of Pregnancy During Pandemic at Pondok Gede Health Centre Bekasi City in 2021 - Andi Julia Rifiana; Ratna Sari (KHD-Production, 2021)
Pregnant women at Pondok Gede Health Center experienced an increase in visits to pregnancies of at-risk mothers in 2019 which consisted of 23 people, while in 2020 there were 103 people. The main cause of pregnancy at risk age is the non- compliance of family planning, the work of WFH during the pandemic. Efforts to reduce risky age pregnancies, BKKBN urges couples of reproductive age to plan pregnancy, using contraception (condoms). The analysis of the causes of increased pregnancy at risk is a large picture of pregnant women with maternal age ≤ 20 years and ≥ 35 years. This research aimed to determine the analysis of the causes of increased pregnancies at risky ages during the pandemic at Pondok Gede Health Center, Bekasi City in 2021. Research analytic by using the method cross-sectional. Sample were 82 respondents with accidental sampling technique. The instrument research was a questionnaire. Data analyzed using univariat and bivariat by test statistic chi square. The result is pregnant women with age ≥ 35 years were 75.6%, who had good knowledge was 54.9%. who have access to family planning services was 53.7%, who were planned was 56.1%, anxiety was 54.9%, who have unmet need pregnancy was 51.2%, and who work WFH was 72,0%. There was no significant relationship between knowledge, access to family planning services, planned pregnancy, anxiety, unmet need pregnancy, work during the pandemic and pregnancy at the age of mothers at risk at Pondok Gede Health Center, Bekasi City with a p value <0.05.